Evaluation of the Library Management System at MA Matsaratul Huda Panempan - Abdullah Ahsan Bashori; Abrori Abrori; Abu Bakar; Rusdiana Navlia (Penerbit Presisi Pustaka, 2026)
The school library is one of the vital components in supporting a quality education process. This study aims to evaluate the library management system at Madrasah Aliyah (MA) Matsaratul Huda Panempan, with a focus on aspects of planning, organizing, implementation, supervision, as well as supporting and inhibiting factors that affect the effectiveness of library management. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. Research informants consist of the school principal, head of the library, librarian, teachers, and students. The results of the study show that the library management system at MA Matsaratul Huda Panempan has been running quite well, especially in terms of work program planning and organizing library collections. However, there are several significant challenges faced, including limited human resources, minimal operational budget, suboptimal information technology infrastructure, and low student reading interest. This study recommends the need to enhance the capacity of librarians through continuous training, optimize the use of digital library information systems such as SLiMS, increase budget allocation, and develop more creative and innovative literacy programs to boost students' reading interest. The findings of this study are expected to serve as a reference for the development of library management in other madrasahs.